cat theory tweaks
authorJim Pryor <profjim@jimpryor.net>
Tue, 2 Nov 2010 13:33:00 +0000 (09:33 -0400)
committerJim Pryor <profjim@jimpryor.net>
Tue, 2 Nov 2010 13:33:00 +0000 (09:33 -0400)
Signed-off-by: Jim Pryor <profjim@jimpryor.net>
advanced_topics/monads_in_category_theory.mdwn

index 768b854..c0d4bf7 100644 (file)
@@ -202,36 +202,36 @@ Let <code>&phi;</code> and <code>&gamma;</code> be members of `T`, that is they
 
 Since composition is associative I don't specify the order of composition on the rhs.
 
-In other words, `<=<` is a binary operator that takes us from two members <code>&phi;</code> and <code>&gamma;</code> of `T` to a composite natural transformation. (In functional programming, at least, this is called the "Kleisli composition operator". Sometimes it's written <code>&phi; >=> &gamma;</code> where that's the same as <code>&gamma; &lt;=&lt; &phi;</code>.)
+In other words, `<=<` is a binary operator that takes us from two members <code>&phi;</code> and <code>&gamma;</code> of `T` to a composite natural transformation. (In functional programming, at least, this is called the "Kleisli composition operator". Sometimes it's written <code>&phi; >=> &gamma;</code> where that's the same as <code>&gamma; <=< &phi;</code>.)
 
-<code>&phi;</code> is a transformation from `F` to `MF'`, where the latter = `MG`; <code>(M &gamma;)</code> is a transformation from `MG` to `MMG'`; and `(join G')` is a transformation from `MMG'` to `MG'`. So the composite <code>&gamma; &lt;=&lt; &phi;</code> will be a transformation from `F` to `MG'`, and so also eligible to be a member of `T`.
+<code>&phi;</code> is a transformation from `F` to `MF'`, where the latter = `MG`; <code>(M &gamma;)</code> is a transformation from `MG` to `MMG'`; and `(join G')` is a transformation from `MMG'` to `MG'`. So the composite <code>&gamma; <=< &phi;</code> will be a transformation from `F` to `MG'`, and so also eligible to be a member of `T`.
 
 Now we can specify the "monad laws" governing a monad as follows:
 
        (T, <=<, unit) constitute a monoid
 
-That's it. Well, there may be a wrinkle here. I don't know whether the definition of a monoid requires the operation to be defined for every pair in its set. In the present case, <code>&gamma; &lt;=&lt; &phi;</code> isn't fully defined on `T`, but only when <code>&phi;</code> is a transformation to some `MF'` and <code>&gamma;</code> is a transformation from `F'`. But wherever `<=<` is defined, the monoid laws are satisfied:
+That's it. Well, there may be a wrinkle here. I don't know whether the definition of a monoid requires the operation to be defined for every pair in its set. In the present case, <code>&gamma; <=< &phi;</code> isn't fully defined on `T`, but only when <code>&phi;</code> is a transformation to some `MF'` and <code>&gamma;</code> is a transformation from `F'`. But wherever `<=<` is defined, the monoid laws are satisfied:
 
 <pre>
-           (i) &gamma; `<=<` &phi; is also in T
+           (i) &gamma; <=< &phi; is also in T
 
-          (ii) (&rho; `<=<` &gamma;) `<=<` &phi;  =  &rho; `<=<` (&gamma; `<=<` &phi;)
+          (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
 
-       (iii.1) unit `<=<` &phi;  =  &phi;                 (here &phi; has to be a natural transformation to M(1C))
+       (iii.1) unit <=< &phi;  =  &phi;                 (here &phi; has to be a natural transformation to M(1C))
 
-       (iii.2)                &phi;  =  &phi; `<=<` unit  (here &phi; has to be a natural transformation from 1C)
+       (iii.2)                &phi;  =  &phi; <=< unit  (here &phi; has to be a natural transformation from 1C)
 </pre>
 
 If <code>&phi;</code> is a natural transformation from `F` to `M(1C)` and <code>&gamma;</code> is <code>(&phi; G')</code>, that is, a natural transformation from `FG` to `MG`, then we can extend (iii.1) as follows:
 
 <pre>
        &gamma; = (&phi; G')
-         = ((unit `<=<` &phi;) G')
+         = ((unit <=< &phi;) G')
          = ((join -v- (M unit) -v- &phi;) G')
          = (join G') -v- ((M unit) G') -v- (&phi; G')
          = (join G') -v- (M (unit G')) -v- &gamma;
          ??
-         = (unit G') `<=<` &gamma;
+         = (unit G') <=< &gamma;
 </pre>
 
 where as we said <code>&gamma;</code> is a natural transformation from some `FG'` to `MG'`.
@@ -240,12 +240,12 @@ Similarly, if <code>&phi;</code> is a natural transformation from `1C` to `MF'`,
 
 <pre>
        &gamma; = (&phi; G)
-         = ((&phi; `<=<` unit) G)
+         = ((&phi; <=< unit) G)
          = (((join F') -v- (M &phi;) -v- unit) G)
          = ((join F'G) -v- ((M &phi;) G) -v- (unit G))
          = ((join F'G) -v- (M (&phi; G)) -v- (unit G))
          ??
-         = &gamma; `<=<` (unit G)
+         = &gamma; <=< (unit G)
 </pre>
 
 where as we said <code>&gamma;</code> is a natural transformation from `G` to some `MF'G`.
@@ -347,7 +347,7 @@ So our **(lemma 2)** is:
 </pre>
 
 
-Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <code>&gamma; &lt;=&lt; &phi;</code> in the monad laws. For simplicity, I'll omit the "-v-".
+Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <code>&gamma; <=< &phi;</code> in the monad laws. For simplicity, I'll omit the "-v-".
 
 <pre>
        for all &phi;,&gamma;,&rho; in T, where &phi; is a transformation from F to MF', &gamma; is a transformation from G to MG', R is a transformation from R to MR', and F'=G and G'=R: